The effect of environmental knowledge and attitudes on decision-making strategies contextualized Sustainable Development Goals (SDGs) in high school student - Annisak Arum Rohmawati; Sukisman Purtadi (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the influence of environmental knowledge and attitudes on decision-making strategies with the context of Sustainable Development Goals (SDGs) among high school students in Sleman Regency. Data were collected using random sampling technique through a survey involving 291 students from public high schools in Sleman Regency using tests to measure environmental knowledge and questionnaires to assess environmental attitudes and decision-making strategies. Instrument validity was tested through theoretical and empirical validity. The results showed that all instruments were valid and reliable. Then, the results of further tests were analyzed using the Structural Equation Modeling (SEM) method which includes the measurement model (measurement model) and strucrutal model (structural model) stages. then analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS4 software. The results of the analysis showed that environmental knowledge (p = 0.744 > 0.05) and environmental attitudes (p = 0.375 > 0.05) did not have a significant influence on students' decision-making strategies.